Transdisciplinary Management Of Islamic Education: Educational Institutions As A Global Sub System - Wijaya, Suzatmiko; Darussalim, Darussalim; Yogaswara, Dody; Azmi, Fachruddin; Sidik, Muhammad; Abdi, Wuri Tamtama (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
Education is a system, namely goals, educators, students, materials, methods or learning media, and the educational environment. Each component has a unique function, and each component benefits other components. In today's world, there are many problems caused by various changes, such as social and religious changes, as well as technological changes, all of which harm education. The method in this article uses library research, namely collecting data by understanding and studying theories from various literature related to the research. There are four stages of library study in research, namely preparing the necessary equipment, preparing a working bibliography, organizing time, and reading or recording research material. This system describes real events and entities, such as places, objects, and people that exist and occur, Input to the Education System The input system for education has been divided into three categories: general input, instrumental input, and local input, The educational process is always influenced by the surrounding environment, Islamic education whose function is as a transfer of valueGlobalization has brought many positive and negative impacts to people from all over the world. The positive impact of the virus can be seen in advances in information and communication technology. Global Insight Education, also called Global Education, provides global information to students to prepare themselves for the era of globalization.   Keywords: Transdisciplinary Management, Islamic Education Institutions, Global Sub System